2022
DOI: 10.1073/pnas.2121400119
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule redistributes iron in ferroportin-deficient mice and patient-derived primary macrophages

Abstract: Deficiencies of the transmembrane iron-transporting protein ferroportin (FPN1) cause the iron misdistribution that underlies ferroportin disease, anemia of inflammation, and several other human diseases and conditions. A small molecule natural product, hinokitiol, was recently shown to serve as a surrogate transmembrane iron transporter that can restore hemoglobinization in zebrafish deficient in other iron transporting proteins and can increase gut iron absorption in FPN1-deficient flatiron mice. However, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Recent studies demonstrated that the natural product hinokitiol acts as a cell-permeant Fe chelator and facilitates Fe redistribution across pathophysiologic gradients in rodents. 25,26 An aqueous formulation of iron pyrophosphate citrate (FPC), which directly replenishes the transferrin-Fe pool upon intravenous infusion, has an FDA indication for use in CKD patients receiving hemodialysis. 27,28 However, care must be taken to ensure that serum FPC concentrations do not exceed transferrin's capacity to bind Fe as exposure to toxic labile Fe occurs above this threshold.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that the natural product hinokitiol acts as a cell-permeant Fe chelator and facilitates Fe redistribution across pathophysiologic gradients in rodents. 25,26 An aqueous formulation of iron pyrophosphate citrate (FPC), which directly replenishes the transferrin-Fe pool upon intravenous infusion, has an FDA indication for use in CKD patients receiving hemodialysis. 27,28 However, care must be taken to ensure that serum FPC concentrations do not exceed transferrin's capacity to bind Fe as exposure to toxic labile Fe occurs above this threshold.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ekaputri et al. ( 5 ) discuss, in PNAS, the biological activity and potential therapeutic use of hinokitiol, a small, plant-derived molecule used in traditional Asian medicine that also has the potential to mobilize iron in the setting of iron overload.…”
mentioning
confidence: 99%
“…The studies of hinokitiol described by Ekaputri et al. ( 5 ) indicate this small molecule works in a fundamentally different way.…”
mentioning
confidence: 99%
See 2 more Smart Citations